2022
DOI: 10.1097/md.0000000000030169
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for frailty in older adults

Abstract: Aims: To clarify the risk factors for frailty to help doctors prevent diseases that cause weakness, through early interventions. Methods: We searched the PubMed, EMBASE, and Cochrane Library databases to identify all relevant studies using the items “frailty,” “weak,” “risk factors,” and “predictive factors” and compared their results. The aging population (≥65 years old) was divided into 2 groups, a “frailty group” and a “robust control group,” and then the characteristics, lifestyles, and comorbidities wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 52 publications
0
34
0
1
Order By: Relevance
“…Older patients also had a lower BMI compared to those younger, with the average BMI of 25 in the >85‐year category. A lower BMI may indicate the presence of frailty within our older patient cohort as indicated by a recent systematic review 8 …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Older patients also had a lower BMI compared to those younger, with the average BMI of 25 in the >85‐year category. A lower BMI may indicate the presence of frailty within our older patient cohort as indicated by a recent systematic review 8 …”
Section: Discussionmentioning
confidence: 85%
“…A lower BMI may indicate the presence of frailty within our older patient cohort as indicated by a recent systematic review. 8 Some studies in the literature have shown that surgeons may offer open surgery to older patients rather than consider laparoscopic procedures due to possible vulnerable cardiopulmonary compliance in older patients as well as the perceived longer operation times. 9,10 Our study found that laparoscopic surgery was performed equally in the elderly population without any evidence of an increase in surgical or respiratory complications.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that there is a statistically strong relationship between undernutrition based on the BMI and MNA scales and frailty as measured by both the Fried phenotypic scale and the Rockwood multidimensional scale, while undernutrition based on albumin level is significantly related to frailty according to the Fried modified SEGA scales. The relationship between undernutrition and frailty syndrome has been demonstrated in previous scientific studies, as indicated by a systematic review of the literature [ 22 ]. Our work highlights the importance of measuring and evaluating undernutrition, as well as frailty syndrome, as they can predict negative events and an increase in morbidity and mortality.…”
Section: Discussionmentioning
confidence: 98%
“…Our study showed that age, BMI, motivation and energy, symptoms and side-effects, self-rated health status, activity level and cognitive impairment were the influencing factors related to frailty in inpatients with SZ. Age and BMI have been shown to be a risk factor for frailty ( 37 , 38 ). “Motivation and energy” and “symptoms and side-effects” were associated with frailty in the present study, indicating that insufficient motivation and energy and severe symptoms and side-effects would increase the risk of frailty.…”
Section: Discussionmentioning
confidence: 99%